Serum exosomal microRNA profiling reveals a down-regulation of hsa-miR-124-3p in patients with severe acne - Zhang, Shujuan; Liang, Yimin; Xia, Manqi; Tian, Xin; Chen, Ziyan; Lin, Ling; Liang, Jingyao; Liu, Yumei (Frontiers in Immunology, 2025)
BackgroundAcne is a chronic inflammatory skin disease affecting pilosebaceous unit. However, its specific mechanism remain incompletely understood.ObjectivesThis study aims to identify and analyze the differential expression of serum exosomal miRNA in severe acne, revealing new insights into the pathogenesis of acne.MethodsMiRNAs were extracted from serum exosomes of 15 patients with severe acne and 15 healthy controls. MiRNA libraries were constructed and sequenced using Illumina HiSeq 2500. The DESeq2R was applied to identify differentially expressed miRNAs. The candidate target genes were predicted using multiple miRNA databases. The DAVID database was used to enrich GO function and KEGG pathway analysis of target genes. Cytoscape3.10.0 was employed to construct a PPI interaction network and further screen hub genes. The most significantly differentially expressed miRNAs were validated using RT-qPCR detection.ResultsSmall RNA-Seq analysis identified a total of 96 serum exosome miRNAs, with 33 up-regulated and 63 down-regulated. Target prediction across four miRNA databases identified 10,569 target genes. GO analysis showed that target genes were mainly enriched in transcriptional regulation, signal transduction and protein binding; KEGG analysis revealed enrichment in 160 pathways including PI3K-Akt and MAPK signaling pathway. Cytoscape 3.10.0 identified 7 hub genes: PIK3R1, PIK3CA, SRC, EGFR, JAK2, ERBB2, and IGF1R, along with 35 corresponding differentially expressed miRNAs. RT-qPCR results indicated a significant reduction in exosomal miR-124-3p levels in severe acne.ConclusionsSerum exosomal miRNA expression in patients with severe acne significantly differed from that in healthy individuals. The exosomal miR-124-3p expression was markedly reduced in severe acne compared to healthy controls. Consequently, the increase of miR-124-3p expression may have potential therapeutic implications for severe acne.